Regional circulation around Heard and McDonald Islands and through the Fawn Trough, central Kerguelen Plateau - van Wijk, EM; Stephen Rintoul; Ronai, BM; Guy Williams (2010)
The fine-scale circulation around the Heard and McDonald Islands and through the Fawn Trough, Kerguelen Plateau, is described using data from three high-resolution CTD sections, Argo floats and satellite maps of chlorophyll a, sea surface temperature (SST) and absolute sea surface height (SSH). We confirm that the Polar Front (PF) is split into two branches over the Kerguelen Plateau, with the NPF crossing the north-eastern limits of our survey carrying 25 Sv to the southeast. The SPF was associated with a strong eastward-flowing jet carrying 12 Sv of baroclinic transport through the deepest part of Fawn Trough (relative to the bottom). As the section was terminated midway through the trough this estimate is very likely to be a lower bound for the total transport. We demonstrate that the SPF contributes to the Fawn Trough Current identified by previous studies. After exiting the Fawn Trough, the SPF crossed Chun Spur and continued as a strong north-westward flowing jet along the eastern flank of the Kerguelen Plateau before turning offshore between 50 degrees S and 51.5 degrees S. Measured bottom water temperatures suggest a deep water connection between the northern and southern parts of the eastern Kerguelen Plateau indicating that the deep western boundary current continues at least as far north as 50.5 degrees S. Analysis of satellite altimetry derived SSH streamlines demonstrates a southward shift of both the northern and southern branches of the Polar Front from 1994 to 2004. In the direct vicinity of the Heard and McDonald islands, cool waters of southern origin flow along the Heard Island slope and through the Eastern Trough bringing cold Winter Water (WW) onto the plateau. Complex topography funnels flow through canyons, deepens the mixed layer and increases productivity, resulting in this area being the preferred foraging region for a number of satellite-tracked land-based predators.